PENGEMBANGAN MEDIA EGG COUNTING BOX BERBASIS GAME BASED LEARNING UNTUK SISWA KELAS 1 SEKOLAH DASAR - Sifha Maharani, Nanda; Harjati, Purwiro; Alfarisi, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted in response to the need for engaging and concrete learning media to support first-grade elementary school students in understanding addition and subtraction concepts. The study aimed to develop an Egg Counting Box learning medium based on the Game-Based Learning approach and to determine its feasibility and practicality for mathematics instruction. The research employed the Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The participants included one media expert, one subject-matter expert, one first-grade teacher, and ten first-grade students at SD Negeri 1 Simbarwaringin. Data were collected through interviews, validation questionnaires, and response questionnaires. The findings indicated that the developed learning medium achieved a feasibility score of 93.75% from the media expert and 84.09% from the subject-matter expert, both categorized as highly feasible. The student response questionnaire showed a practicality score of 86.50%, while the teacher response questionnaire reached 91.25%, indicating that the medium was highly practical for classroom use. These findings suggest that the Game-Based Learning-based Egg Counting Box is both highly feasible and highly practical as an instructional medium for teaching addition and subtraction of numbers from 1 to 20 in first-grade elementary school mathematics. The developed medium can serve as an alternative learning resource to enhance students' engagement and understanding of mathematical concepts.